PENGKAJIAN STUDI LITERATUR PERENCANAAN KESEHATAN DAN KESELAMATAN KERJA (K3) DI PLTD JUNGKAT - Tendean, Roni; Pratiwi, Riyanni; Syahrudin, - (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2017)
The construction service industry is one of the sectors that has a high accident risk. It can not just be left to mind the losses that will not only cause casualties, material that is not the least good for workers and employers, delayed production process, until the damage to the environment that ultimately affect the public. That is why the required Occupational Safety and Health Management (K3) implemation on all construction work. The purpose of this research is to examine the implementation and implementation of K3 in Jungkat PLTD. Data analysis used quantitative analysis using primary data from interview, observation, literature study, questionnaire, sample and data analysis. The mean yand obtained from the data analysis of the importance level of the K3 program in general is 3.53 with a standard deviation of 0.22. the average of the six K3 program factors is 3.02 with a standard deviation of 0.37. In order for the construction project to run smoothly and not be hampered by the existence of work accidents, it should be in the implementation of the company should be more implemented OSH program. Keywords: Construction, application, Accident